2017
DOI: 10.1002/pds.4326
|View full text |Cite
|
Sign up to set email alerts
|

Using probability of drug use as independent variable in a register‐based pharmacoepidemiological cause‐effect study—An application of the reverse waiting time distribution

Abstract: The pattern of high ORs and narrow confidence intervals in probabilistic exposure measures is compatible with less nondifferential misclassification of exposure than in a dichotomous exposure model. Probabilistic exposure measures appear to be an attractive alternative to conventional exposure measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…For the two last approaches, we kept all generated individuals in the analysis to maintain comparability of standard errors with the other analyses, even though it is common practice in pharmacoepidemiologic studies to only include individuals which have no observed prescription redemptions (the reference group) or are classified as exposed (i.e. have a redemption inside the prespecified main exposure window) [ 3 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the two last approaches, we kept all generated individuals in the analysis to maintain comparability of standard errors with the other analyses, even though it is common practice in pharmacoepidemiologic studies to only include individuals which have no observed prescription redemptions (the reference group) or are classified as exposed (i.e. have a redemption inside the prespecified main exposure window) [ 3 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…In simulation studies and an empirical validation study for Warfarin, the method provided estimates with low bias, unless the model was severely misspecified [ 1 , 2 ]. In a recent study, we suggested to use the reverse WTD to estimate the probability of being exposed on the index date, and use this probability as exposure variable [ 3 ]. The objective was to better allow for the fact that the actual exposure status is not recorded, and that the analyst may therefore introduce misclassification bias when forcing a dichotomy upon exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have a redemption inside the prespecified main exposure window). (1,6) For each method and setting we estimated the median relative bias of the estimated OR, the median standard error of the log-OR, the coverage probability of nominal 95% confidence intervals and finally the relative variance inflation factor with respect to the optimal analysis when exposure status is directly observed.…”
Section: Simulation Studymentioning
confidence: 99%
“…In a recent study, we suggested to use the reverse Waiting Time Distribution (WTD) to estimate the probability of being exposed on the index date, and use this probability as exposure variable. (1) The objective was to better allow for the fact that the actual exposure status is not recorded, and that the analyst may therefore introduce misclassification bias when forcing a dichotomy upon exposure. The approach was intended to directly represent the analyst's uncertainty about actual exposure by using probability of being exposed as exposure covariate.…”
Section: Introductionmentioning
confidence: 99%